Determinants of the Acceptance of Ambon City Local Government Information Systems using the Technology Acceptance Model - Sherly Toding; Evi Maria (Sistemasi: Jurnal Sistem Informasi, 2023)
The research aims to find empirical evidence on the determinants of the acceptability of Ambon City regional apparatus on implementing the Regional Government Information System (SIPD) using the Technology Acceptance Model (TAM). The research sample is SIPD users in Ambon City, with a total sample of 90 respondents. This research data was collected from a questionnaire that was measured using a Likert scale. Data were analyzed using simple linear regression analysis. The research results found empirical evidence that the perceived convenience of SIPD users affected perceptions of SIPD use in Ambon City and attitudes towards using SIPD in Ambon City, and attitudes towards SIPD use had an effect on actual SIPD use in Ambon City. This research did not find evidence of an influence between perceptions of the usefulness of SIPD on attitudes towards using SIPD in Ambon City. It means that the Ambon City regional apparatus will use SIPD in supporting development planning and regional financial management work if the apparatus perceives that SIPD is easy to use. If the regional apparatus accepts SIPD, then the regional apparatus will use the SIPD to manage development activities in Ambon City. Therefore, the government of Ambon City can be more active in socializing SIPD and holding training programs for SIPD users so that local officials can use SIPD optimally to support planning and financial management work.Keywords:. local government information system, Technology Acceptance Model, acceptability of regional apparatus.